FOREIGN POLICY STRATEGY OF THE ISLAMIC REPUBLIC OF IRAN - Kuchkarov , Temirbek (Educational Research in Universal Sciences, 2023)
The article provides information about the main directions of the foreign policy of the Islamic Republic of Iran, what are the foreign political strategies and the role of these strategies in the life of the society today.